If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(-4x+2)-6x=3(x-5)-6
We move all terms to the left:
-6(-4x+2)-6x-(3(x-5)-6)=0
We add all the numbers together, and all the variables
-6x-6(-4x+2)-(3(x-5)-6)=0
We multiply parentheses
-6x+24x-(3(x-5)-6)-12=0
We calculate terms in parentheses: -(3(x-5)-6), so:We add all the numbers together, and all the variables
3(x-5)-6
We multiply parentheses
3x-15-6
We add all the numbers together, and all the variables
3x-21
Back to the equation:
-(3x-21)
18x-(3x-21)-12=0
We get rid of parentheses
18x-3x+21-12=0
We add all the numbers together, and all the variables
15x+9=0
We move all terms containing x to the left, all other terms to the right
15x=-9
x=-9/15
x=-3/5
| 8p-2=23 | | 7(k+8)=70 | | -4x+-8x=12 | | -6x-60+8x+20=92 | | 2a+7+6a=55 | | (5y-7)=180 | | 125m-75m+39000=40600-150m | | 25/4x=7 | | 4x+8+90=180 | | 19-5x/2=-16 | | 4k-(-7)=11 | | 6-3x/4=-5 | | 9z+13=-8 | | 4x+8^0+90=180 | | 9x+7+3x=43 | | g-10+7g=15+4g | | 0=-4.5t^2-18t+15 | | 7(x+8)+6=7x+9 | | 125m-75m+39000=40600-50m | | -b=28 | | 9x+5=10x−4 | | -3(2+4)=4w-5 | | 7x+3=12x-24 | | -3m+-7=2 | | 6x–1=19 | | -0.55x+0.25x=6.6 | | 7x-4=-21 | | 5x(x+3)=1/3(9x+18)-5 | | 4x-5x=x-29 | | 2v-5=10 | | 21m=150 | | X+3+x=X+10 |